Integrating bioremediation of textile wastewater with biodiesel production using microalgae (Chlorella vulgaris). (October 2021) - Fazal, Tahir; Rehman, Muhammad Saif Ur; Javed, Fahed; Akhtar, Mueed; Mushtaq, Azeem; Hafeez, Ainy; Alaud Din, Aamir; Iqbal, Javed; Rashid, Naim; Rehman, Fahad
Abstract: Microalgae-led wastewater treatment is a promising biorefinery approach to promote environmental and economical sustainability. In this study, Chlorella vulgaris ( C . vulgaris ) was employed for the bioremediation of textile wastewater (TWW) and biodiesel production. C . vulgaris is cultivated in undiluted and diluted TWW (50%). Cultivation in freshwater containing BG11 medium was set as a control. Results show the highest growth (1.62 ± 0.12 OD680 ) in diluted TWW followed by BG11 medium (1.56 ± 0.15 OD680 ) and undiluted TWW (0.89 ± 0.11 OD680 ). The highest methylene blue decolorization of 99.7% was observed in diluted TWW as compared to 98.5% in undiluted TWW. Morever, COD removal efficiency was also higher (99.7 ± 4.2%) in diluted TWW than BG11 medium (94.4 ± 3.5%) and undiluted TWW (76.3 ± 2.8%). For all treatment, more than 80% nitrogen and phosphorous removal were achieved. Otther than this, fatty acids methyl ester (FAME) yield in diluted TWW was higher (11.07 mg g −1 ) than the undiluted TWW (9.12 mg L −1 ). Major FAME were palmitic acid (C16:0) and linolenoic acid (C18:3) which are suitable for biodiesel production. All these results suggest that C . vulgaris can be cultivated in both diluted and undiluted TWW for biodiesel production. However, cultivation in undiluted TWW is more favorable as it displaces the need for freshwater addition in the growth medium. Graphical abstract: Image 1 Highlights: Microalgae cultivation is integrated with textile wastewater (TWW) treatment. Microalgae could grow and produce algal oil both in undiluted and diluted TWW. Microalgae removed 99% dye in diluted TWW. COD removal increased up to 99% in diluted TWW. Total 11.07 mg g −1 fatty acid methyl esters (FAME) yield was achieved in diluted TWW.